2015
DOI: 10.1021/acsami.5b01077
|View full text |Cite
|
Sign up to set email alerts
|

“Elastic” Property of Mesoporous Silica Shell: For Dynamic Surface Enhanced Raman Scattering Ability Monitoring of Growing Noble Metal Nanostructures via a Simplified Spatially Confined Growth Method

Abstract: ABSTRACT:The Raman enhancing ability of noble metal nanoparticles (NPs) is an important factor for surface enhanced Raman scattering (SERS) substrate screening, which is generally evaluated by simply mixing as-prepared NPs with Raman reporters for Raman signal measurements. This method usually leads to incredible results because of the NP surface coverage nonuniformity and reporter-induced NP aggregation. Moreover, it cannot realize in situ, continuous SERS characterization. Herein, we proposed a dynamic SERS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…When the volume of AgNO 3 was increased to 100 μL, an anisotropic Ag coating occurred, leading to the tags with an orange slice-like shape ( Figure 2B). This anisotropic growth feature was consistent with Au/Ag NR growth from bare AuNR, 27,36 which indicated that the adsorbed Raman reporters did not influence the growth behavior of the silver shells. When the volume was increased to more than 300 μL, the tags became spherical and their size increased ( Figure 2C−E).…”
Section: ■ Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…When the volume of AgNO 3 was increased to 100 μL, an anisotropic Ag coating occurred, leading to the tags with an orange slice-like shape ( Figure 2B). This anisotropic growth feature was consistent with Au/Ag NR growth from bare AuNR, 27,36 which indicated that the adsorbed Raman reporters did not influence the growth behavior of the silver shells. When the volume was increased to more than 300 μL, the tags became spherical and their size increased ( Figure 2C−E).…”
Section: ■ Introductionsupporting
confidence: 71%
“…On the other hand, the silver shell of AuNR/Ag core/shell NPs evolved from homogeneous to special anisotropic coatings on AuNRs with increasing amounts of silver. 27 This would make the SERS signal evolution of the tags complicated. Moreover, AuNR was capped by a dense long-chain cetyltrimethylammonium bromide (CTAB) bilayer, which led to difficulties in Raman reporter adsorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As shown in the literature, core@shell structures 12,13 and array substrates 14,15 have emerged as promising approaches for meeting these requirements of both effective enhancement and acceptable reproducibility. As shown in the literature, core@shell structures 12,13 and array substrates 14,15 have emerged as promising approaches for meeting these requirements of both effective enhancement and acceptable reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This tunability of GNRs can be further enriched by collective plasmon coupling through the formation of periodic arrays of GNRs, [6,7] and thus provides potential applications such as sensors, [8][9][10][11][12][13] broadband absorbers, [14] plasmonic catalysts, [15] and other plasmonic devices. [1][2][3][4][5] This tunability of GNRs can be further enriched by collective plasmon coupling through the formation of periodic arrays of GNRs, [6,7] and thus provides potential applications such as sensors, [8][9][10][11][12][13] broadband absorbers, [14] plasmonic catalysts, [15] and other plasmonic devices.…”
Section: Introductionmentioning
confidence: 99%